Store Atmosphere Analysis Moderates the Effect of Food and Beverage Quality and Service Quality on Consumer Satisfaction at Atlas Coffee and Bike in Pekanbaru City - Handayani, Widya; Fahmi, Irham; Mahdi, Sayed; Zulfadli (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2022)
The purpose of this study is to see and understand consumer behavior in the food and beverage business from the literature side of the study on store atmosphere which moderates the influence of food and beverage quality and service quality on customer satisfaction at Atlas Coffee and Bike in Pekanbaru City. The results showed that the store atmosphere, the quality of food and beverage services affect customer satisfaction at Atlas Coffee and Bike. In this study using the operational method of variables consisting of exogenous and endogenous variables where the exogenous variables are Store Atmosphere (X1), Food and Beverage Quality (X2), Service Quality (X3), then the endogenous variable is Consumer Satisfaction (Y). Consumers have full expectations to enjoy the atmosphere at Atlas Coffee and Bike to the fullest and want satisfaction, moreover the food and beverage business has dimensions that are more than just basic consumption needs but also want a recreational atmosphere. The results of this study are very useful for management, it can increase revenue and expect consumers to make repeat visits.